Analisis Pemanfaatan Bioteknologi pada Tanaman Padi Hasil Rekayasa Genetika : Studi Literatur (Indo-MathEdu Intellectuals Journal, 2026)
Modern biotechnology, particularly genetic engineering, has been widely utilised in agriculture to improve the productivity and quality of food crops, including rice. This study aims to analyse the use of genetic engineering biotechnology in rice crops and its contribution to increasing agricultural yields and food security. The research method used was a literature study, reviewing various scientific journal articles discussing the application of genetically engineered rice. The results of the study show that genetic engineering in rice plants can increase resistance to pests and diseases, tolerance to extreme environmental conditions, and higher yields. However, its application still faces a number of challenges, including food safety issues, potential environmental impacts, and public acceptance. Thus, the use of genetic engineering biotechnology in rice plants has great potential in supporting sustainable agriculture, but it needs to be accompanied by clear regulations, strict supervision, and continuous socialisation to the public.